EXPLORATION STUDENTS’ LEVEL PROACTIVE DECISION MAKING (PDM) BASED ON METACOGNITIVE SKILL IN SOLVING REACTION RATE PROBLEMS (UNESA Journal of Chemical Education, 2017)
This research has aim to describe and analyse students’ level Proactive Decision Making (PDM) based on metacognitive skill in solving reaction rate problems for upper, middle, and lower students’ groups in chemistry subject. The subjects in this research is students XI-Light Vehicle Technique (Teknik Kendaraan Ringan) in Vocational High School (Sekolah Menengah Kejuruan) Kudu Jombang. This is qualitative research, the data source are students’ evaluation test results and interviews. The validation method that use is method and times triangulation. The Proactive Decision Making (PDM) level are Object, Alternative, Information, and Decision Radar. The results showed that students’ level Proactive Decision Making (PDM) in the planning stage upper group has the highest level, which is Decision Radar, middle group is Information, and lower group is Alternative. The monitoring stage level of the three groups is Decision Radar, and the reflection stage level of the three groups is Object. Keyword: proactive decision making, metacognitive skill, problem solving